Konstruksi Identitas Virtual Melalui Media Sosial: Kajian Dramaturgi pada Akun Facebook Rima Susanti - Yayu R. Mayangsari; Firdaus Firdaus; Rahmi Rahmi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Social media has now changed the way individuals construct, display, and manage their identities in public spaces. Rima Susanti's professional Facebook account is interesting to study using Ervin Goffman's dramaturgical theory because it represents a person's identity in the digital world. The purpose of this study is to determine how dramaturgy works behind the management of Rima Susanti's professional Facebook account. This study uses a descriptive qualitative approach. The study was conducted by observing the contents of "Rima Susanti's" Facebook social media. Data collection techniques were taken through interviews, observations, and documentation. In the analysis of research data content, data analysis techniques were carried out based on an interactive analysis model. The results of this study are Facebook as Rima Susanti's digital front stage. She emphasizes her image as a funny, hardworking, and stylish content creator on her Facebook account. This can be seen from the funny videos she makes and posts on her Facebook account to get many likes and comments from her followers. However, from her various posts that entertain people, on the backstage Rima leaves her attributes and identity as a comedy content creator and behaves without any particular impression management. Rima Susanti is herself as a single mother who tries to support her two children by working as a content creator, trader and a farmer.